Mutagenicity of 2-hydroxyamino-1-methyl-6-phenylimidazo[4, 5-b]pyridine (N–OH-PhIP) in human TP53 knock-in (Hupki) mouse embryo fibroblasts. (January 2021) - Hölzl-Armstrong, Lisa; Moody, Sarah; Kucab, Jill E.; Zwart, Edwin P.; Bellamri, Medjda; Luijten, Mirjam; Turesky, Robert J.; Stratton, Michael R.; Arlt, Volker M.; Phillips, David H.
Abstract: 2-Amino-1-methyl-6-phenylimidazo[4, 5- b ]pyridine (PhIP) is a possible human carcinogen formed in cooked fish and meat. PhIP is bioactivated by cytochrome P450 enzymes to form 2-hydroxyamino-1-methyl-6-phenylimidazo[4, 5- b ]pyridine ( N –OH-PhIP), a genotoxic metabolite that reacts with DNA leading to the mutation-prone DNA adduct N -(deoxyguanosin-8-yl)-PhIP (dG-C8-PhIP). Here, we studied N –OH-PhIP-induced whole genome mutagenesis in human TP53 knock-in (Hupki) mouse embryo fibroblasts (HUFs) immortalised and subjected to whole genome sequencing (WGS). In addition, mutagenicity of N –OH-PhIP in TP53 and the lacZ reporter gene were assessed. TP53 mutant frequency in HUF cultures treated with N –OH-PhIP (2.5 μM for 24 h, n  = 90) was 10% while no TP53 mutations were found in untreated controls (DMSO for 24 h, n  = 6). All N –OH-PhIP-induced TP53 mutations occurred at G:C base pairs with G > T/C > A transversions accounting for 58% of them. TP53 mutations characteristic of those induced by N –OH-PhIP have been found in human tumours including breast and colorectal, which are cancer types that have been associated with PhIP exposure. LacZ mutant frequency increased 25-fold at 5 μM N –OH–PHIP and up to ~350 dG-C8-PhIP adducts/10 8 nucleosides were detected by ultra-performance liquid chromatography-electrospray ionisation multistage scan mass spectrometry (UPLC-ESI-MS 3 ) at this concentration. In addition, a WGS mutational signature defined by G > T/C > A transversions was present in N –OH-PhIP-treated immortalised clones, which showed similarity to COSMIC SBS4, 18 and 29 signatures found in human tumours. Highlights: N –OH-PhIP induced 10% TP53 -mutants in immortalised HUFs. A WGS mutational signature was extracted after N –OH-PhIP treatment. The TP53 mutation pattern and WGS mutational signature are characterised by G > T/C > A transversions. TP53 mutations N –OH-PhIP-exposed HUFs could be related to those found in human tumours. The WGS mutational signature shows similarity to COSMIC SBS4, 18 and 29 suggesting that PhIP is involved in liver and colorectal carcinogenesis.